Stochastic multi-objective programming for simultaneous clearing of energy and spinning reserve markets considering reliability preferences of customers - Amirahmadi, Meysam; Akbari Foroud, Asghar (International journal of electrical power & energy systems, 2013)
•A new simultaneous energy and SR markets clearing model is presented.•ISO is not further responsible for determining and procuring the required SR.•DISCOs declare VOLLs to SR market and subscribe desired SR in every contingency.•Subscribed SR of a DISCO is not only dependant on the amount of its VOLL.•DISCO’s position in network and power demand can affect the subscribed SR. Determination and procurement of required Spinning Reserve (SR) capacity have ever been major concerns in the power industry. In restructured power systems in various countries, Independent System Operators (ISO) determine the SR capacity requirements based on different criteria and procure the estimated SR on behalf of customers from SR market. In this paper a new stochastic joint energy and SR market clearing model is presented based on a multi-objective mixed integer nonlinear programming with three objective functions. In the proposed model the customers participate in SR market directly by declaring the Value of Lost Load (VOLL) and acquire the required SR. The responsibility of ISO to SR market is restricted to two proceedings; minimizing the total Expected Load Not Supplied (ELNS) of the power system and maximizing the post-contingency expected social welfare associated with the SR scheduling at the first and second objective functions. Meanwhile the pre-contingency offered cost is minimized at the third one. Simulation results from two test cases are presented to back up the conclusions.